Towards passive bioremediation of dye-bearing effluents using hydrous ferric oxide wastes: Mechanisms, products and microbiology. (1st September 2022) - Srivastava, Pallavee; Al-Obaidi, Safaa A.; Webster, Gordon; Weightman, Andrew J.; Sapsford, Devin J.
Abstract: A novel, circular economy-inspired approach for the "passive" (non-powered and reagent-free) treatment of dye-bearing effluent is presented. The treatment utilises the biogeochemical interaction of dye-bearing wastewater with hydrous ferric oxide (HFO) bearing sludges. The work presented demonstrates for the first time the reuse of HFO-rich waste sludges from potable water and mine water treatment. The waste was used directly without modification or reagent addition, as media/substrate in simple flow-through reactors for the decolourisation and biodegradation of methyl orange (MO) and mixed dyes textile effluent. Three phases of exploratory proof of concept work were undertaken. Columns containing HFO sludges were challenged with solution of MO, and MO amended with glycerol (Phase I), MO in a synthetic textile effluent recipe (Phase II), and real mixed textile effluent containing a mixture of dyes (Phase III). After an initial lag period extensive decolourisation of dye was observed in all cases at rates comparable with pure strains and engineered bioreactor processes, with evidence of biodegradation beyond simple cleavage of the mono azo chromophore and mineralisation. The microbiology of the initial sludge samples in both cases exhibited a diverse range of iron oxidising and reducing bacteria. However, post experiment the microbiology of sludge evolved from being dominated by Proteobacteria to being dominated by Firmicutes . Distinct changes in the microbial community structure were observed in post-treatment MWTS and WTWS where genera capable of iron and sulphate reduction and/or aromatic amine degradation were identified. Average nitrogen removal rates for the columns ranged from 27.8 to 194 g/m 3 /day which is higher than engineered sequential anaerobic-aerobic bioreactor. Postulated mechanisms for the fast anaerobic decolourisation, biodegradation, and mineralisation of the dyes (as well nitrogen transformations) include various direct and indirect enzymatic and metabolic reactions, as well as reductive attack by continuously regenerated reductants such as Fe(II), HFO bound Fe(II), FeS, and HS − . The ability of iron reducers to degrade aromatic rings is also considered important in the further biodegradation and complete mineralisation of organic carbon. The study reveals that abundant and ubiquitous HFO-rich waste sludges, can be used without amendment, as a substrate in simple flow-through bioremediation system for the decolourisation and partial biodegradation of dyes in textile effluent. Highlights: Passive treatment of dye bearing wastewater with hydrous ferric oxide rich sludges is demonstrated. Simple flow-through reactors achieve efficient dye decolourisation. Significant nitrogen removal along with complete biodegradation of dye is obtained. Distinct changes in microbial community structure were observed post experiment. Genera capable of Fe/SO4 2− reduction and aromatic amine degradation were observed.